Characterization of Propagation Phenomena Relevant for 300 GHz Wireless Data Center Links - Cheng, Chia-Lin; Zajic, Alenka (IEEE transactions on antennas and propagation, 2020)
This article presents details about an extensive channel measurement campaign and subsequent statistical channel models for the characterization of 300 GHz channels for wireless rack-to-rack (R2R) and blade-to-blade (B2B) communications in a data center-like environment. Measurements were conducted in various scenarios such as R2R line-of-sight (LoS), R2R obstructed-LoS (OLoS), R2R reflected-non-LoS (RNLoS), R2R obstructed-RNLoS (ORNLoS), B2B RNLoS, B2B ORNLoS, and B2B LoS scenarios. In the aforementioned scenarios, we explored the impact of transmitter (Tx)/receiver (Rx) misalignment and obstructions such as cables, metal cabinets, and mesh structures on terahertz (THz) propagation, as well as feasibility of using existing metal objects as reflectors for NLoS links. For the R2R LoS scenario, an optical lens was used to extend the Tx-Rx separation distance. This led to a waveguide effect in the channels measured thereby resulting into a path loss exponent (PLE) of 1.48 with a shadowing gain of 0.7 dB. When obstructions of cables are present, ORNLoS link outperforms OLoS link with 2.5 dB lower shadowing gain and weaker multipath. Reflector in the RNLoS link has reflection coefficients very close to 1 for all incident angles. For the B2B scenario, a dual-reflector THz transceiver rack system is proposed to enable wireless links across vertically stacked servers and allow easy maintenance and repair of servers. The measured path loss closely follows the Friis values in the LoS link and in the RNLoS link with hollow vertical ground plane. When obstructions of cables are present, the ORNLoS link experiences 5-10 dB higher path loss and on average 0.25 GHz lower coherence bandwidth than the RNLoS link. The measured statistical channel properties show that the shadowing gain caused by cable clusters follows the log-normal distribution.